Planificación para mantener la integridad del Sistema de Gestión de la Calidad durante los cambios en la empresa Mejía Asociados S.A. (2009)
Mejía Asociados S.A got the ISO 9001: 2000 certificate in 2007, for all Core Business processes. At 2008 this company decides to transform this processes in specialized companies, in order to increase the marketing area, the business units earnings and the products enhancement and optimization, increasing profit. Due to this transition, the integrity of the QMS (Quality Management System) was in danger, so it was necessary to reduce the organization trauma, according to the ISO 9001:2000 5.4.2 numeral, in order to avoid its disintegration.